Method of Making the Decision to Find the Optimal Technological Alternative to Treat the Demolition Waste in the Syrian Case - Bassam Hassan; Jamal Omran; Hassan Ali (Tishreen University, 2020)
One of the worst consequences of the war on Syria is significant destruction of infrastructure and urban buildings. That requires deep investigation and needs to think seriously how to deal with the rubble from the destroyed buildings and to separate the ruins of these buildings for several categories according to the types; concrete, masonry, stones, iron, wood and aluminum. It is very important to benefit as possible as the most of these materials in the reconstruction to prevent booking large landfill to store them useless and pose an economic and environmental impact and distort the general view of the country, so it's very important to use it in good manner in future. This study presents method of estimation expected debris size in some Syrian cities and the components of these debris and the cost of recycling and expected profits by proposing a plan of action in the field of management of recycling debris, And select the appropriate technological alternative to implement this plan.